Sequential Investment, Hold-up and Strategic Delay - ZHANG, Juyuan (Institutional Knowledge at Singapore Management University, 2010)
We investigate hold-up with simultaneous and sequential investment. We show that if the encouragement effect of sequential complementary investments dominates the delay effect, sequential investment alleviates the underinvestment caused by the hold-up problem. Further, if it is allowed to choose when to invest, strategic delay occurs when the encouragement effect of sequential complementary investments dominates the delay effect.